Amino Acids As Mediators of Metabolic Cross Talk between Host and Pathogen - Ren, Wenkai; Rajendran, Ranjith; Zhao, Yuanyuan; Tan, Bie; Wu, Guoyao; Bazer, Fuller W.; Zhu, Guoqiang; Peng, Yuanyi; Huang, Xiaoshan; Deng, Jinping; Yin, Yulong (Frontiers in Immunology, 2018)
The interaction between host and pathogen decidedly shapes the outcome of an infection, thus understanding this interaction is critical to the treatment of a pathogen infection. Although research in this area has yielded surprising findings in cell biology regarding interactions between host and pathogen, we have limited understanding of the metabolic crosstalk between host and pathogen. At the site of infection, host and pathogen share similar or identical nutritional substrates and generate common metabolic products, thus metabolic crosstalk between host and pathogen could profoundly affect the pathogenesis of an infection. In this review, we will present results regarding a recent discovery of a metabolic interaction between host and pathogen with amino acids (AA) metabolism-centric point of view. The host depends on AA metabolism to support defensive responses against the pathogen, while the pathogen modulates AA metabolism for its own advantage. Some AA, such as arginine, asparagine and tryptophan, are central points of competition between the host and pathogen. Thus, a better understanding of AA-mediated metabolic crosstalk between host and pathogen will provide insight into fruitful therapeutic approaches to manipulate and prevent progression of an infection.